2022
DOI: 10.2196/30720
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Data–Based Patient Similarity Framework for Patient Outcome Prediction: Algorithm Development

Abstract: Background Sequential information in electronic medical records is valuable and helpful for patient outcome prediction but is rarely used for patient similarity measurement because of its unevenness, irregularity, and heterogeneity. Objective We aimed to develop a patient similarity framework for patient outcome prediction that makes use of sequential and cross-sectional information in electronic medical record systems. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…We found that the endto-end and similarity-based approaches showed comparably low predictive performance for any number of clusters k ranging from 2 to 8. This finding is in contrast with previous studies, [8][9][10] where the similarity-based approach led to performance benefits. One possible explanation is that the available clinical and demographic variables were not strong predictors of changes in PHQ-9 scores in our data set.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that the endto-end and similarity-based approaches showed comparably low predictive performance for any number of clusters k ranging from 2 to 8. This finding is in contrast with previous studies, [8][9][10] where the similarity-based approach led to performance benefits. One possible explanation is that the available clinical and demographic variables were not strong predictors of changes in PHQ-9 scores in our data set.…”
Section: Discussioncontrasting
confidence: 99%
“…The idea behind this approach is that we try to better capture the heterogeneity of patient characteristics by bypassing the need to create a single, complex model, valid for all possible patient subgroups and types. The two-stage method has previously yielded improved predictive performance compared with the usual end-to-end approach in some applications, such as for predicting mortality and readmission in patients with acute myocardial infarction and for diagnosis and outcome prediction in patients with kidney diseases 9 10. It remains however unclear whether applying this method in other settings, such as in mental health outcomes prediction, may also lead to improved performance.…”
Section: Introductionmentioning
confidence: 99%
“…We maintained patients’ first hospitalization data to evaluate the proposed method. Demographic data (age and gender) and the following AMI-related features were maintained in both data sets: AMI-relevant items of laboratory tests that at least 95% of patients carried out, AMI-relevant radiological features extracted from radiology reports [ 34 ], 7 commonly prescribed medications, and all recorded disease diagnoses and procedures. For laboratory tests performed more than once, only the results obtained in the first test (usually at admission) were retained, which could reflect a patient’s health status and the severity of illness.…”
Section: Methodsmentioning
confidence: 99%
“…Information 40,87,88,89], mortality [90], risks [91], and patient outcomes [89,92,93]. IE and prediction tasks will certainly continue to perform on clinical and health data in the next years.…”
Section: Typical Nlp Tasks: Ie and Predictionmentioning
confidence: 99%